Correlation Between Physical Activity and Happiness: A Cross-Sectional Study in Medan - Aufa Awalia Said; Eka Roina Megawati; Evita Mayasari; Farhat (Sumatera Medical Journal, 2026)
Introduction: Physical activity contributes to mental well-being by stimulating neurotransmitters associated with pleasure and positive mood. Understanding this relationship within specific populations is important for promoting community health. Objective: This study aimed to evaluate the correlation between physical activity and happiness among residents of Medan, Indonesia. Methods: This cross-sectional study was conducted in Medan from May to November 2021 and involved 260 participants. Physical activity was assessed using the International Physical Activity Questionnaire, while happiness and affect were measured using the Oxford Happiness Questionnaire and the Positive and Negative Affect Scale. Data were analyzed using Spearman’s rank correlation test. Results: Overall physical activity was positively correlated with happiness (r = 0.132; p = 0.034) and positive affect (r = 0.214; p = 0.001). Vigorous physical activity showed positive correlations with happiness (r = 0.185; p = 0.003) and positive affect (r = 0.244; p = 0.001). Walking was also positively correlated with happiness (r = 0.132; p = 0.034) and positive affect (r = 0.214; p = 0.001). Moderate physical activity was not correlated with happiness (r = –0.017; p > 0.05) or positive affect (r = 0.065; p > 0.05). No correlation was found between physical activity and negative affect. Conclusions: Physical activity is positively correlated with happiness among residents of Medan.